Defending the "people of truth" in the early Islamic period : the Christian apologies of Abū Rī́íaiṭah - Keating, Sandra Toenies (History of Christian-Muslim relations ;, 2006)
This volume contains the apologetical writings of Ab? R?'i?ah al-Takr?t? (c. 835) devoted to the defense of the Christian doctrines of the Trinity and Incarnation, and the proof of the Christian religion in response to Muslim critics of his time.